Are You a Lehman, Brother? Interbank Uncertainty in a DSGE Model - Christian Grimme; Thomas Siemsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Did the increase in counterparty risk perception in the interbank market since autumn 2007 contribute to the severe contraction of the US economy? To address this question we introduce interbank market uncertainty in a DSGE model with frictional financial intermediation. Interbank uncertainty is modeled as exogenous change in the dispersion of beliefs about the fraction of interbank loans expected to be repaid. In our model higher uncertainty in wholesale banking leads to reductions in interbank lending activities as banks become more funding constraint. This induces a deleveraging process which reduces loans to firms and investment severely.
Keywords: E32; E37; E17; 330